Encyclopedia of Analytical Chemistry 2020
DOI: 10.1002/9780470027318.a9931.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Plant Steroids: Occurrence, Biological Significance, and Their Analysis

Abstract: Plant steroids constitute a diverse group of natural products. Biosynthetically, they are derived from S ‐squalene‐2,3‐epoxide via acetate‐mevalonate pathway. Among the plant steroids, phytosterols are ubiquitous in the plant kingdom and some of them are reported to possess hypocholesterolemic activity. Withanolides are a large group of steroidal lactones with various biological activities. Brassinosteroids are a small group of plant steroids classified as plant growth hormones. Phytoec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 113 publications
0
4
0
1
Order By: Relevance
“…substituents at C-10 and C-13 and alkyl substituent at C-17. The oxidation states of these tetracyclic carbon cores and methyl groups and their structure chain exhibit immense chemical diversity of steroids (Gunaherath & Gunatilaka, 2020). Based on taxonomic considerations and biological structures, plant steroids can be classified into seven major classes (Kreis & Müller-Uri, 2018) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…substituents at C-10 and C-13 and alkyl substituent at C-17. The oxidation states of these tetracyclic carbon cores and methyl groups and their structure chain exhibit immense chemical diversity of steroids (Gunaherath & Gunatilaka, 2020). Based on taxonomic considerations and biological structures, plant steroids can be classified into seven major classes (Kreis & Müller-Uri, 2018) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Phytosterols represent a large family of naturally occurring lipophilic compounds found in the cell membranes of plants and they have an important role in the regulation of many cellular functions [103,104]. It has been reported that the phytosterols, such as β-sitosterol, stigmasterol, and lanosterol (Figure 8), were identified in the tissue of A. cepa [105].…”
Section: Steroidsmentioning
confidence: 99%
“…This makes the screening of saponins needs adjustment on the temperature. Steroids are compounds that are composed of four fused rings and are categorized into a few types [18]. Some of them serve as functional hormones which for example estrogen, progesterone, corticoids, and androgen.…”
Section: Introductionmentioning
confidence: 99%